Relationship between Penicillin-Binding Proteins Alterations and β-Lactams Non-Susceptibility of Diseased Pig-Isolated Streptococcus suis - Kamonwan Lunha; Wiyada Chumpol; Surasak Jiemsup; Sukuma Samngamnim; Pornchalit Assavacheep; Suganya Yongkiettrakul (MDPI AG, 2023)
Streptococcus suis is a zoonotic pathogen causing disease in both animals and humans, and the emergence of increasingly resistant bacteria to antimicrobial agents has become a significant challenge globally. The objective of this study was to investigate the genetic basis for declining susceptibility to penicillin and other β-lactams among S. suis. Antimicrobial susceptibility testing and penicillin-binding proteins (PBP1a, PBP2a, PBP2b, and PBP2x) sequence analysis were performed on 225 S. suis isolated from diseased pigs. This study found that a growing trend of isolates displayed reduced susceptibility to β-lactams including penicillin, ampicillin, amoxicillin/clavulanic acid, and cephalosporins. A total of 342 substitutions within the transpeptidase domain of four PBPs were identified, of which 18 substitutions were most statistically associated with reduced β-lactams susceptibility. Almost all the S. suis isolates which exhibited penicillin-non-susceptible phenotype (71.9%) had single nucleotide polymorphisms, leading to alterations of PBP1a (P409T) and PBP2a (T584A and H588Y). The isolates may manifest a higher level of penicillin resistance by additional mutation of M341I in the 339STMK active site motif of PBP2x. The ampicillin-non-susceptible isolates shared the mutations in PBP1a (P409T) and PBP2a (T584A and H588Y) with additional alterations of PBP2b (T625R) and PBP2x (T467S). The substitutions, including PBP1a (M587S/T), PBP2a (M433T), PBP2b (I428L), and PBP2x (Q405E/K/L), appeared to play significant roles in mediating the reduction in amoxicillin/clavulanic acid susceptibility. Among the cephalosporins, specific mutations strongly associated with the decrease in cephalosporins susceptibility were observed for ceftiofur: PBP1a (S477D/G), PBP2a (E549Q and A568S), PBP2b (T625R), and PBP2x (Q453H). It is concluded that there was genetically widespread presence of PBPs substitutions associated with reduced susceptibility to β-lactam antibiotics.